2013
DOI: 10.1038/bjc.2013.430
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implication of the CpG island methylator phenotype in colorectal cancers depends on tumour location

Abstract: Background:Colorectal cancer (CRC) is usually categorised as proximal or distal CRC. Recently, many researchers have tried to determine the molecular heterogeneity of CRCs along bowel subsites. However, the differential effects of the CpG island methylator phenotype (CIMP) and microsatellite instability (MSI) on the clinical outcome according to tumour location are not well-known.Methods:We analysed clinicopathologic and molecular characteristics, including CIMP, MSI, KRAS and BRAF mutations, in 734 CRCs accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
2
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 58 publications
(76 reference statements)
2
78
2
3
Order By: Relevance
“…When subgroup analysis was performed, CIMP was found to be an indicator of poor prognosis only in MSS, and not in MSI tumors (comparable to BRAF mutation status). These data are well in the line with an earlier study by Bae et al [72], who noted prognostic implications of CIMP status only in distal tumors.…”
Section: Microsatellite Instability In Sporadic Colorectal Cancersupporting
confidence: 93%
“…When subgroup analysis was performed, CIMP was found to be an indicator of poor prognosis only in MSS, and not in MSI tumors (comparable to BRAF mutation status). These data are well in the line with an earlier study by Bae et al [72], who noted prognostic implications of CIMP status only in distal tumors.…”
Section: Microsatellite Instability In Sporadic Colorectal Cancersupporting
confidence: 93%
“…This has been shown in patient studies, where CIMP-H was shown to associate with older female patients, smoking, proximal location, MSI-H tumours and BRAF mutations [10]. This study also noted a proximal location of CIMP-H tumours, and this has been reported in other studies where it was suggested that CIMP-H and MSI-H increase from the rectum to the caecum [26]. This is interesting as it is thought there is a similar distribution of local inflammation across CRC tumours, and CIMP-H/MSI-H/BRAF mutant tumours are also associated with an increase in intra-tumour inflammation characterised by a lymphocytic infiltration [8].…”
Section: Cms1: Msi Immunesupporting
confidence: 85%
“…This study demonstrated that the frequencies of CIMP-high, MSI-high, and BRAF and PIK3CA mutations in colorectal cancer increase gradually from rectum to ascending colon, challenging the notion of an acute transition at the splenic flexure (131). Independent studies have confirmed similar distributions in molecular features of colorectal cancers (34, 161163). Furthermore, in synchronous colorectal cancers, molecular similarities are proportional to the physical proximity of the two cancers (164).…”
Section: Colorectal Continuummentioning
confidence: 74%